Health Education is Important for Increasing the Knowledge of Students in SD N 1 Suwug to Maintaining Reproductive Health - Putu Sukma Megaputri; Ni Made Karlina Sumiari Tangkas; Made Bayu Oka Widiarta; Indrie Lutfiana (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The rise of cases of sexual harassment and sexual violence against children demands that children be immediately given information about reproductive health, prevention of sexual violence to organ function and how to look after it. The purpose of this service is to provide health education regarding reproductive health to children at SD N 1 Suwug to increase their knowledge in maintaining reproductive health. The stages of implementing community service are divided into three stages, namely planning, implementation and monitoring and evaluation. With a target number of 106 students located in SD N 1 Suwug. The result was that there was an increase in knowledge before and after being given reproductive health education to children and all of the targets enthusiastically wanted to know the function of their respective reproductive organs. The conclusion is that health education, especially reproductive health in elementary school children, is a necessity to form self-responsibility for their respective reproductive organs.